2017
DOI: 10.1146/annurev-neuro-072116-031109
|View full text |Cite
|
Sign up to set email alerts
|

Neural Circuitry of Reward Prediction Error

Abstract: Dopamine neurons facilitate learning by calculating reward prediction error, or the difference between expected and actual reward. Despite two decades of research, it remains unclear how dopamine neurons make this calculation. Here we review studies that tackle this problem from a diverse set of approaches, from anatomy to electrophysiology to computational modeling and behavior. Several patterns emerge from this synthesis: that dopamine neurons themselves calculate reward prediction error, rather than inherit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

18
280
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 315 publications
(317 citation statements)
references
References 126 publications
18
280
1
Order By: Relevance
“…While our data demonstrate that the caloric content of food rapidly entrains the inhibition of AgRP neurons as a response to food cues, the function of this rapid sensory inhibition remains unknown. Since these neurons transmit a negative valence signal to drive food intake (Betley et al, 2015), it is possible that the rebound in AgRP neuron activity that occurs when a non-nutritive substance is identified serves as a reward prediction error (Schultz et al, 1997; Watabe-Uchida et al, 2017) that devalues non-food substances. This would be conceptually similar to the function of dopamine neurons in the ventral tegmental area, that first fire upon presentation of a reward, but over time fire instead at presentation of a cue predicting a reward.…”
Section: Discussionmentioning
confidence: 99%
“…While our data demonstrate that the caloric content of food rapidly entrains the inhibition of AgRP neurons as a response to food cues, the function of this rapid sensory inhibition remains unknown. Since these neurons transmit a negative valence signal to drive food intake (Betley et al, 2015), it is possible that the rebound in AgRP neuron activity that occurs when a non-nutritive substance is identified serves as a reward prediction error (Schultz et al, 1997; Watabe-Uchida et al, 2017) that devalues non-food substances. This would be conceptually similar to the function of dopamine neurons in the ventral tegmental area, that first fire upon presentation of a reward, but over time fire instead at presentation of a cue predicting a reward.…”
Section: Discussionmentioning
confidence: 99%
“…For example, they could be provided by direct feedback from the aforementioned higher-order cortical areas, or they could be derived from sub-cortical areas that are implicated in attention and behavioral updating during learning (Wimmer et al, 2015). Modulatory reinforcement signals that are associated with behavioral outcome could also play a major role (Pi et al, 2013;Watabe-Uchida et al, 2017). Indeed, reward-related response modulation has been observed in S1 (Lacefield et al, 2019), and was found to promote cortical plasticity processes related to visual response tuning in primary visual cortex (Goltstein et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Besides these "phasic" responses, dopamine neurons typically maintain relatively low and stable baseline firing rates between these events. These response patterns have been observed in a number of animal species and in different task conditions (Bayer and Glimcher, 2005;Clark et al, 2012;Watabe-Uchida et al, 2017;Wenzel et al, 2015), and the RPE hypothesis has greatly impacted our understanding of dopamine functions in the brain. However, many of these experiments have employed relatively simple behavioral paradigms using discrete stimuli and outcomes.…”
Section: Introductionmentioning
confidence: 95%